Multi-hop interactive attention based classification network for expert recommendation - Qian, Lingfei; Wang, Jian; Lin, Hongfei; Yang, Liang; Zhang, Yu (Neurocomputing (Amsterdam), 2022)
Community question answering (CQA) is a popular platform where users can ask questions or solve the questions proposed by other users. The expert recommendation aims at providing high-quality answers for the newly proposed questions in time, which is the key to a successful CQA. Questions in CQA usually consist of two parts, a subject which describes the main point, and a body which gives the details of the question. In previous studies, researchers usually ignore the differences between the subject and the body and concatenate them as a whole. In this paper, we propose a multi-hop interactive attention based classification network (MIACN) to recommend experts for newly proposed questions. In our model, the subject and the body are seen as two separate parts. A multi-hop attention is used to capture the multiple latent interactions among the two parts. Then, a high-level representation of the question is generated from the interactions. Experiment results on two real-world datasets demonstrate the effectiveness of our model.